2021
DOI: 10.1111/odi.13798
|View full text |Cite
|
Sign up to set email alerts
|

The ambiguous role of sirtuins in head and neck squamous cell carcinoma

Abstract: Oral cancer is one of the most leading cancer responsible for significant morbidity and mortality. The sirtuins (SIRTs) are a family of class III histone deacetylases and are known to regulate a variety of molecular signaling associated with different cancer types including oral malignancies. SIRT1 acts as bifunctional in a variety of cancer. In oral cancer, SIRT1 seems to work as a tumor suppressor. The carcinogenic potential of SIRT1 is also reported in oral cancer, and hence, its role is still ambiguous.SIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(65 citation statements)
references
References 70 publications
0
65
0
Order By: Relevance
“…Devaraj et al reported that both the tumor suppressor role and carcinogenic role of SIRT1 are reported in oral cancer, so its role is still ambiguous. In oral cancer, SIRT2 is not studied enough and so its role remains obscure (Ezhilarasan et al, 2021). There was no statistically significant difference between dysplastic oral leukoplakia, non-dysplastic oral leukoplakia, and control groups; all showed statistically significantly lower SIRT-1 levels than the OSCC group.…”
Section: +Pv: Positive Predictive Value -Pv: Negative Predictive Valuementioning
confidence: 91%
“…Devaraj et al reported that both the tumor suppressor role and carcinogenic role of SIRT1 are reported in oral cancer, so its role is still ambiguous. In oral cancer, SIRT2 is not studied enough and so its role remains obscure (Ezhilarasan et al, 2021). There was no statistically significant difference between dysplastic oral leukoplakia, non-dysplastic oral leukoplakia, and control groups; all showed statistically significantly lower SIRT-1 levels than the OSCC group.…”
Section: +Pv: Positive Predictive Value -Pv: Negative Predictive Valuementioning
confidence: 91%
“…Our team has extensive knowledge and research experience that has translated into high-quality publications [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Surface wettability has an important role in many biological, chemical and physical processes.…”
Section: Discussionmentioning
confidence: 99%
“…Our team has extensive knowledge and research experience that has translated into high quality publications [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]26,27]. Composite materials can degrade due to any mechanical or chemical factors from the oral environment including the composition of saliva, masticatory stress exerted, toothpaste used, force of brushing, textures of food particles etc [28].…”
Section: Methodsmentioning
confidence: 99%